Role of Hepcidin in Anemia of Chronic Disease in Rheumatoid Arthritis - Nita, Eleni; Bairaktari, Eleni; Kolios, George; Migkos, Michail P.; Somarakis, Georgios-Petros; Markatseli, Theodora; Archimandriti, Dimitra; Tsaousi, Christina; Voulgari, Paraskevi V. (Journal of Laboratory Physicians, 2021)
Objective Anemia of chronic disease is a frequent consequence in rheumatoid arthritis and is associated with major clinical and patient outcomes. The present cross-sectional study explored the role of hepcidin (HEP) in anemia of chronic disease in rheumatoid arthritis by studying its relationships with markers of anemia, iron metabolism, inflammation, and erythropoiesis.Methods Blood samples from anemic (n = 43) and nonanemic (n = 43) rheumatoid arthritis patients were analyzed for markers of anemia (hemoglobin, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, red cells distribution width, and reticulocyte hemoglobin), iron metabolism (iron, total iron binding capacity, ferritin, transferrin saturation, soluble transferrin receptor), inflammation (erythrocyte sedimentation rate, C-reactive protein, and interleukin 6), and erythropoiesis (erythropoietin and HEP). Correlation analysis was used to identify relationships between HEP and all other variables. Principal component analysis was used to identify common underlying dimensions representing linear combinations of all variables.Results HEP had statistically significant mostly moderate-to-large correlations with markers of anemia (0.30–0.70, all p < 0.01), small correlation with markers of iron metabolism and markers of inflammation (r = 0.20–0.40, all p < 0.01), and moderate correlations with markers of erythropoiesis. Principal component analysis revealed two underlying components (factors) capturing approximately 50% of total variability. Factor 1 comprised mainly of markers of anemia, iron metabolism, and erythropoiesis and was related to “erythrocyte health status,” while factor 2 comprised mainly markers of inflammation and iron metabolism and was related to “acute phase reactants.” HEP was the only variable demonstrating substantial loadings on both factors.Conclusions HEP is related to markers of anemia, iron metabolism, inflammation, and erythropoiesis. In addition, when all variables are “reduced” to a minimum number of two “latent” factors, HEP is loaded on both, thus underlying its pivotal role in the complex interaction of the erythropoietic response in inflammation-induced anemia and/or functional iron deficiency.
Keywords: principal component analysis; iron; functional iron deficiency; dimension reduction